👤

scrie inversul lui x
x=( -[tex]\sqrt{14}[/tex] + 2[tex]\sqrt{10}[/tex] ):[tex]\sqrt{2}[/tex] + (6[tex]\sqrt{15[/tex] -8[tex]\sqrt{21}[/tex] ) : (-2[tex]\sqrt{3}[/tex] )


Răspuns :

Răspuns:

Explicație pas cu pas:

[tex]=-\sqrt{7} +2\sqrt{5}-3\sqrt{5}+4\sqrt{7}=3\sqrt{7}-\sqrt{5}[/tex]

[tex]\frac{1}{x} =\frac{1}{3\sqrt{7} -\sqrt{5} }=\frac{3\sqrt{7}+\sqrt{5}}{(3\sqrt{7}-\sqrt{5})(3\sqrt{7}+\sqrt{5})} =\frac{3\sqrt{7}+\sqrt{5}}{(3\sqrt{7})^{2}-(\sqrt{5})^{2} }=\frac{3\sqrt{7} +\sqrt{5}}{63-5}= \frac{3\sqrt{7} +\sqrt{5}}{58}[/tex]

x = [tex]\it (-\sqrt{14} + 2\sqrt{10}) : \sqrt{2} + (6\sqrt{15} - 8\sqrt{21}) : (-2\sqrt{3} )[/tex]

x = [tex]\it -\sqrt{7} + 2\sqrt{5} - 3\sqrt{5} + 4\sqrt{7}[/tex]

x = [tex]\it 3\sqrt{7} - \sqrt{5}[/tex]

[tex]\it ~^{3\sqrt{7} + \sqrt{5}) } \frac{1}{3\sqrt{7} - \sqrt{5}  } = \frac{3\sqrt{7} + \sqrt{5}  }{(3\sqrt{7})^{2} - (\sqrt{5})^{2} } = \frac{3\sqrt{7} + \sqrt{5} }{63 - 5} = \frac{3\sqrt{7} + \sqrt{5} }{58}[/tex]